Efforts to Improve Learning Readiness Through Virtual-Based Group Guidance Services Using Role Playing Techniques in Junior High School Students - Krisnanda, Veno Dwi; Izati, Maydana; Husna, Ainul; Karin, Larasati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This research was conducted to determine the effect of increasing learning readiness through virtual-based group guidance services with role playing techniques. The choice of topic with this technique is interesting because it sees the situation that is happening there. Therefore, the researchers tried to do this research using a quantitative approach with a pre-experimental method, in which students in the sample class had problems regarding their learning readiness. For sampling using random sampling. The number of samples in this study were 48 students. The results of the hypothesis test using the paired sample t-test which can be seen from the test results, that the significance value (2-tailed) 0.002 < 0.005 indicates a significant difference between the initial variable and the final variable. This means that there is a significant effect on the treatment given to each variable in the study.